2013
DOI: 10.1109/ted.2013.2256426
|View full text |Cite
|
Sign up to set email alerts
|

Single-Event Burnout Hardening of Power UMOSFETs With Optimized Structure

Abstract: This paper gives and explains the simulation results of single-event burnout (SEB) hardening in a power metaloxide semiconductor field-effect transistor U-Shape Metal Oxide Semiconductor Field Effect Transistor (trench-gate MOSFET). It includes p + plug enlargement and adds a buffer layer that is between the epitaxial layer and substrate. These two hardening solutions are compared and the optimized structure that can prevent SEB is given. The single event gate-rupture (SEGR) threshold voltages in different lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Worst case response may not occur with the incident ion perpendicular to the die surface, but the worst case may be at beam angles almost parallel to the die surface [21]. Wang et al in other work [22] have used TCAD simulation to explore SEB hardening strategies for UMOSFETs. Simulations indicated that enlarging the p + plug and the addition of a buffer layer between the epitaxial layer and substrate can reduce SEB susceptibility with the buffer layer making the most difference.…”
Section: Single Event Burnout (Seb) Effects In Umos Technologymentioning
confidence: 99%
“…Worst case response may not occur with the incident ion perpendicular to the die surface, but the worst case may be at beam angles almost parallel to the die surface [21]. Wang et al in other work [22] have used TCAD simulation to explore SEB hardening strategies for UMOSFETs. Simulations indicated that enlarging the p + plug and the addition of a buffer layer between the epitaxial layer and substrate can reduce SEB susceptibility with the buffer layer making the most difference.…”
Section: Single Event Burnout (Seb) Effects In Umos Technologymentioning
confidence: 99%
“…Many hardening solutions to SEB of power DMOSFETs have been extensively investigated and tested these years. For power UMOSFETs [22]- [24], the research of SEB characteristic, especially for how to design hardened structure to prevent SEB need to be studied [25]. The Schottky contact is often used to improve the reverse recovery characteristics in power MOSFETs [26], [27].…”
Section: Introductionmentioning
confidence: 99%
“…Previous literature has extensively investigated many potential hardening techniques to improve the SEE survivability of trench MOSFET which is also known as power U-shape Metal Oxide Semiconductor Field Effect Transistor (UMOSFET) [7][8][9][10][11][12]. Previous solutions are mainly focused on the Radiation Hardened by Design (RHBD) techniques to mitigate the radiation effects in UMOSFET.…”
Section: Introductionmentioning
confidence: 99%